A new species of Sclerocephalus with a fully ossified endocranium gives insight into braincase evolution in temnospondyls. (November 2021) - Schoch, Rainer R.; Sobral, Gabriela
Abstract: The late Paleozoic temnospondyl Sclerocephalus formed an aquatic top predator in various central European lakes of the late Carboniferous and early Permian. Despite hundreds of specimens spanning a wide range of sizes, knowledge of the endocranium (braincase and palatoquadrate) remained very insufficient in Sclerocephalus and other stereospondylomorphs because even large skulls had unossified endocrania. A new specimen from a stratigraphically ancient deposit at St. Wendel in southwestern Germany is recognized as representing a new taxon, S. concordiae new species, and reveals a completely ossified endocranium. The sphenethmoid was completely ossified from the basisphenoid to the anterior ethmoid region, co-ossified with the parasphenoid, and the basipterygoid joint was fully established. The pterygoid bears a slender, S-shaped epipterygoid, which formed a robust pillar lateral to the braincase. The massive stapes was firmly sutured to the parasphenoid. In the temnospondyl endocranium, character evolution involved various changes in the epipterygoid region, which evolved distinct morphologies in each of the major clades. UUID: http://zoobank.org/5e6d2078-eacf-4467-84cf-a12efcae7c0b